Análisis del proceso de comunicación de la estrategia y su influencia en las políticas de calidad en la industria textil ecuatoriana: un estudio de caso - Nájera, Santiago (2018)
The process of communication the business strategy and its influence on the quality policies is a key issue to be studied. The case study method is a valid alternative to carry out an exhaustive qualitative investigation that allows to obtain a significant understanding of the specific case.